THE SOLUBILITY OF H2O AND CO2 IN RHYOLITIC MELTS IN EQUILIBRIUM WITH A MIXED CO2-H2O FLUID PHASE - Tamic N.; Behrens H.; Holtz F. (My University, 2001)
H2O and CO2 solubilities in a natural rhyolite melt (Erevan Dry Fountain (EDF), Armenia) in equilibrium with H2O-CO2 fluids were determined at 200 and 500 MPa and at 800°C and 1100°C. The composition of the fluid phase after experiment was determined by gravimetry, except for extreme CO2-rich fluids for which mass balance was used. Water and CO2 contents of the glasses were measured using IR spectroscopy. At 200 MPa, the water solubility changes from a square root dependence on mole fraction of H2O in the fluid phase (XH2Of) at low XH2Of to a linear dependence above XH2Of=0.25. Up to about 5 wt.% dissolved water in the melt (corresponding to XH2Of~0.5), a similar trend is observed at 500 MPa. At higher XH2Of, however, the dependence of water solubility on XH2Of is more pronounced than at 200 MPa. A negative temperature dependence of water solubility is observed in the whole experimental range at 200 MPa (e.g. the water solubility at XH2Of=1 decreases from 5.97 to 5.58 wt.% when temperature rises from 800°C to 1100°C). In contrast, at 500 MPa the temperature dependence of water solubility changes from positive at high XH2Of (e.g., increase from 9.84 to 11.04 wt.% for a temperature increase from 800 to 1100°C) to negative at low XH2Of. An empirical model to predict water solubility in rhyolitic melts in the P-T range 75-500 MPa and 800-1100°C was derived from our new solubility data and data from Blank et al. (1993). The model reproduces the data at 75 and 200 MPa within +/-2.5% relative and the data at 500 MPa within +/-5% relative.The CO2 solubility shows a non-linear dependence on XH2Of with deviation from linearity, which increases with pressure. The maximum CO2 solubilities (equilibrium with pure CO2) predicted from the data trends are 0.11+/-0.01 and 0.28+/-0.03 wt.% at 1100°C and 200 Mpa and 500 MPa, respectively. The temperature dependence of CO2 solubility is found to be almost negligible at 200 MPa and slightly positive at 500 MPa. Our solubility data at 200 MPa are reproduced slightly better by the model of Papale (1999) than by that of Holloway and Blank (1994).
Keywords: RHYOLITIC MELT; WATER SOLUBILITY; CO2 SOLUBILITY; INFRARED SPECTROSCOPY; MIXED FLUID